"Transformation Tuesday": Temporal context and post valence influence the provision of social support on social media. Issue 4 (4th July 2018) - Vogel, Erin A.; Rose, Jason P.; Crane, Chantal
ABSTRACT: Social network sites (SNSs) such as Facebook have become integral in the development and maintenance of interpersonal relationships. Users of SNSs seek social support and validation, often using posts that illustrate how they have changed over time. The purpose of the present research is to examine how the valence and temporal context of an SNS post affect the likelihood of other users providing social support. Participants viewed hypothetical SNS posts and reported their intentions to provide social support to the users. Results revealed that participants were more likely to provide social support for posts that were positive and included temporal context (i.e., depicted improvement over time; Study 1). Furthermore, this research suggests that visual representations of change over time are needed to elicit social support (Study 2). Results are discussed in terms of their practical implications for SNS users and theoretical implications for the literature on social support and social media.